Enhancing Adolescent Mental Health Literacy: Strategies for Stigma Reduction and Help-Seeking Behavior - Yani, Ahmad (Yayasan Sinergi Kawula Muda, 2024)
Mental health literacy plays a crucial role in fostering adolescent well-being by enhancing knowledge, reducing stigma, and encouraging help-seeking behaviors. This study examines the effectiveness of mental health literacy interventions and their impact on adolescent perceptions and behaviors. Using a qualitative research design, data were collected through in-depth interviews, focus group discussions, and observations among adolescents in Palu, Central Sulawesi, Indonesia. Thematic analysis identified key themes: emotional turbulence and social expectations, diverse responses to mental health challenges, and the role of education and support systems. Findings suggest that school-based interventions and family engagement significantly improve mental health literacy. However, cultural stigma and gender disparities persist as major barriers. Digital platforms were identified as influential but require structured guidance to enhance reliability. The study underscores the need for holistic, culturally sensitive, and gender-responsive approaches to mental health education. Policy recommendations include integrating mental health literacy into educational curricula and community programs. Further research should explore long-term intervention effectiveness and cross-cultural applicability.